Untimely Dancing - Notes on the micropolitics of movement (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article consists in a reflection on the aesthetic and political powers of dance, in what it overpasses the autonomous art field and meddles in the constitutional processes of subjectivities and places. Starting from the contemporary dance practice and from a somatic analysis of what it can give us to sense and to think, we propose an articulation of two concepts, contemporary and choreography, in order to anchor a broader reflection on the micropolitics of dance.
Keywords: dance; contemporary; choreography; coreopolitics